Estrategias de mitigación de factores psicosociales de riesgo en la cooperativa de ahorro y crédito interandina., 2023. - Sanchez Miranda, Celio David (2023)
The presence of psychosocial risk factors in companies is increasingly having a significant impact on the mental and emotional health of employees, which can have a negative impact on their performance, productivity and work environment. Some of the main psychosocial risk factors in the workplace include work content, workload and pace, work time, participation and control, work climate, social support, recognition and job security. This research was developed with the purpose of determining strategies to mitigate psychosocial risk factors in Cooperativa de Ahorro y Crédito Interandina. This is a descriptive study with a quantitative approach, to diagnose the dimensions of Psychosocial Risk the F-PSICO 4.1 was used as a measurement instrument, which is an evaluation tool created by the National Institute of Safety and Health at Work (INSST) of Spain. The research was carried out with 62 employees of the different agencies in Ambato, Salcedo, Riobamba, Quito and Ibarra of the Cooperative. The diagnosis found that the cooperative has a high risk at national level in the dimensions of workload, participation and supervision, role performance, relationships and social support; therefore, a program was proposed for the dimensions of highest risk, which allows the mitigation of these factors in the Cooperativa de Ahorro y Crédito Interandina with activities.